PERSEPSI GEN Z TERKAIT ETIKA PADA UNGGAHAN AKUN TIKTOK @EKIDAREHANF - Nadifa Aprilia Salsabilla; Tanisya Farah Nabilla; Saifuddin Zuhri; Syalomita Nadia Putri (Jurnal Prodi Ilmu Komunikasi, 2023)
People now have a lot of access to communicate, one of which is to use social media. Social media is often used as a place to express emotions such as anger, insults, insults to cyber bullying. one of which happened to the phenomenon of the @ekidarehanf tiktok content which caused criticism from the public for this content. The aims of this study is to find out how Gen Z perceives ethics in uploading the tiktok account @ekidarehanf. The method used in this study is descriptive qualitative with in-depth interview techniques as a data source. The results of this study are that as a public figure it is better to reflect good behavior because on social media self-identity can be assessed from the behavior reflected on the social media.